The Impact of Hypomania on Aerobic Capacity and Cardiopulmonary Functioning—A Case Report - Shoval, Aura; Armstrong, Hilary F.; Vakhrusheva, Julia; Ballon, Jacob S.; Bartels, Matthew N.; Kimhy, David (Frontiers in Psychiatry, 2018)
Background: Hypomanic episodes are characterized by increased goal-directed behavior and psychomotor agitation. While the affective, cognitive, and behavioral manifestations of such episodes are well documented, their physiological influence on aerobic capacity and cardiopulmonary functioning are unknown. Methods: We describe a case report of an individual with schizophrenia who experienced a hypomanic episode while serving as a control participant (wait list) in a single-blind, randomized clinical trial examining the impact of aerobic exercise on neurocognition in people schizophrenia. As part of the trial, participants completed two scheduled clinical assessments and cardiopulmonary exercise tests (VO2max) at baseline and 12 weeks later at end of study. All participants received standard psychiatric care during the trial. Following a baseline assessment in which he display no evidence of mood lability, the subject returned on Week 12 for his scheduled follow-up assessment displaying symptoms of hypomania. He was able to complete the follow-up assessment, as well as third assessment two weeks later (Week 14) when his hypomanic symptoms ebbed. Results: While not engaging in aerobic exercise training, the subject’s aerobic capacity, as indexed by VO2max, increased by 33% from baseline to Week 12. In comparison, participants engaged in the aerobic exercise training increased their aerobic capacity on average by 18%. In contrast, participants in the control group displayed a small decline (-0.5%) in their VO2max scores. Moreover, the subject’s aerobic capacity increased even further by Week 14 (49% increase from baseline), despite the ebbing of his hypomania symptoms and his return to clinical baseline at that time. Conclusions: Hypomanic episodes lead to substantial increases in aerobic capacity that remain sustained for several weeks, even following the ebbing of hypomanic symptoms. Such elevations may be attributed to increased mobility and goal-directed behavior associated with hypomania, as individuals in hypomanic states may ambulate more frequently, for longer duration, and/or at higher intensity. Our results provide a unique view into the impact of hypomania cardiopulmonary functioning.